2004
DOI: 10.1093/bja/aeh099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postoperative bladder distension and urinary retention detected by ultrasound measurement

Abstract: Before discharge from the recovery room it seems worthwhile to systematically check the bladder volume with a portable ultrasound device in patients with risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 7 publications
9
90
1
8
Order By: Relevance
“…Several studies, though implicating intrathecal anesthesia as a risk factor for urinary retention, neither discuss a comparative anesthetic modality nor provide the dose/type of local anesthetic utilized. 28,30,33,36,41,43,[52][53][54][55] Results of studies assessing the urodynamic effects of both intrathecal local anesthetics and opioids tend to concur with our data. Kamphuis et al performed filling cystometric studies in 30 male patients to estimate detrusor pressure and flow rates.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies, though implicating intrathecal anesthesia as a risk factor for urinary retention, neither discuss a comparative anesthetic modality nor provide the dose/type of local anesthetic utilized. 28,30,33,36,41,43,[52][53][54][55] Results of studies assessing the urodynamic effects of both intrathecal local anesthetics and opioids tend to concur with our data. Kamphuis et al performed filling cystometric studies in 30 male patients to estimate detrusor pressure and flow rates.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the literature across other surgical specialities including orthopaedics, thoracic, vascular and otolaryngology; where neither gender has been consistently identified to confer risk [49][50][51]54 .…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
“…Eight studies in this review demonstrated increased age as a risk factor for POUR, a finding which has been shown following many types of surgery in the ambulatory and inpatient settings 1,[49][50][51][52][53] . Sub-group analysis demonstrated a marked increase in the risk of POUR once an age cut-off of ≥60 years was used.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 67%
“…Lee et al [6] defined POUR as the inability to urinate or a residual urine volume of more than 100 ml after selfvoiding for two days after surgery. It has been reported that a normal bladder volume is 400-600 ml in healthy adults and that individuals begin to feel the sense of voiding at a bladder volume of 150 ml [17]. When bladder volume reaches 300 ml, patients feel a sense of urinary urgency.…”
Section: Discussionmentioning
confidence: 99%